Genotypic and Phenotypic Variability for Yield and its Components in Normal and Late Sown Chickpea (Cicer arietinum L.) - Yücel, Derya (AGRICULTURAL RESEARCH COMMUNICATION CENTRE, 2020)
Chickpea (Cicer arietinum L.) is one of the important legumes widely grown for dietary proteins in semi-arid Mediterranean climatic conditions. The main goal of any breeding programs in the world is to produce high yield and better quality genotypes for farmers and commercial growers to be released as cultivars. Present research has been conducted to select more desirable characteristics that may contribute to the improvement of drought tolerant chickpea. Thirty-two chickpea genotypes along with two control varieties were evaluated in winter and late sowing conditions in 2015 and 2016, in randomized complete block design with three replications. Phenotypic coefficients of variation were found to be higher than genotypic coefficients of variation for all the traits. The highest heritability along with high genetic advance was found for hundred seed weight followed by podding day, plant height, flowering day and first pod height in normal and stress conditions. These traits can be improved by giving special attention during selection.
Keywords: Cicer arietinum; Genotypic variability; Heritability; Seed yield